Analysis of Production Technology of Marmalade and Pastille Products - Barnokhon Sattarova; Aziza Makhmudova (Genius Journals, 2023)
This article presents ideas about the production of marmalade and pastilla products, the technology of making marmalade.
Keywords: marmalade; lozenge; jelly marmalade; fruit-berry marmalade